Physiological characterization of the wild almond Prunus arabica stem photosynthetic capability - Trainin, Taly; Brukental, Hillel; Shapira, Or; Attia, Ziv; Tiwari, Vivekanand; Hatib, Kamel; Gal, Shira; Zemach, Hanita; Belausov, Eduard; Charuvi, Dana; Holland, Doron; Azoulay-Shemer, Tamar (Frontiers in Plant Science, 2022)
Leaves are the major plant tissue for transpiration and carbon fixation in deciduous trees. In harsh habitats, atmospheric CO2 assimilation via stem photosynthesis is common, providing extra carbon gain to cope with the detrimental conditions. We studied two almond species, the commercial Prunus dulcis cultivar ‘Um-el-Fahem’ and the rare wild Prunus arabica. Our study revealed two distinctive strategies for carbon gain in these almond species. While in P. dulcis, leaves possess the major photosynthetic surface area, in P. arabica, green stems perform this function in particular during the winter after leaf drop. These two species' anatomical and physiological comparisons show that P. arabica carries unique features that support stem gas exchange and high gross photosynthetic rates via stem photosynthetic capabilities (SPC). On the other hand, P. dulcis stems contribute low gross photosynthesis levels, as they are designed solely for reassimilation of CO2 from respiration, which is termed stem recycling photosynthesis (SRP). Results show that a) P. arabica stems are covered with a high density of sunken stomata, in contrast to the stomata on P. dulcis stems, which disappear under a thick peridermal (bark) layer by their second year of development. b) P. arabica stems contain significantly higher levels of chlorophyll compartmentalized to a mesophyll-like, chloroplast-rich, parenchyma layer, in contrast to rounded-shape cells of P. dulcis’s stem parenchyma. c) Pulse amplitude modulated (PAM) fluorometry of P. arabica and P. dulcis stems revealed differences in the chlorophyll fluorescence and quenching parameters between the two species. d) Gas exchange analysis showed that guard cells of P. arabica stems tightly regulate water loss under elevated temperatures while maintaining constant and high assimilation rates throughout the stem. Our data show that P. arabica uses a distinctive strategy for tree carbon gain via stem photosynthetic capability, which is regulated efficiently under harsh environmental conditions, such as elevated temperatures. These findings are highly important and can be used to develop new almond cultivars with agriculturally essential traits.